A Framework for the Comparative Analysis of Music Theory Textbooks - Ádám MIKE (Studia Universitatis Babeş-Bolyai. Musica, 2025)
This study proposes a novel framework for the comparative analysis of music theory textbooks, with particular focus on harmony instruction in Hungarian secondary-level music education. The research addresses a critical gap in both national and international scholarship: despite the acknowledged pedagogical importance of textbooks, no comprehensive comparative analysis exists that evaluates their structural and didactic dimensions within the discipline of music theory. Drawing from Ágnes Dárdai’s influential work in textbook analysis, the study adapts her comparative methodology to meet the specific demands of music pedagogy. The analysis is structured into three methodological phases: macrostructural examination, microstructural analysis of selected chapters, and evaluation of thematic coherence with particular attention to the treatment of chords borrowed from the parallel minor. This framework contributes to the evolving discourse on textbook theory, curricular alignment, and the role of disciplinary specificity in educational materials.